Community Empowerment through Training on Determining Fish Production Costs for Strengthening the Marine Resource-Based Economy - MF Arrozi Adhikara; Sugiyanto Sugiyanto; Sri Handayani; Jatmiko Jatmiko; Fachmi Tamzil; Adrie Putra (GUYUB: Journal of Community Engagement, 2026)
. This community service program was conducted to address inaccuracies in the calculation of the Cost of Production (COP) among Cuwe fish cracker home industries on Tidung Island, Thousand Islands, Jakarta. Most business actors calculated production costs conventionally and often excluded maintenance, electricity, and packaging expenses from factory overhead costs, resulting in underestimated production costs and less accurate pricing decisions. Therefore, the program aimed to improve participants’ understanding of COP calculation and equip them with practical skills to determine production costs systematically in order to strengthen business competitiveness. The program adopted a Participatory Action Research (PAR) approach involving 18 home-industry actors and was implemented through four stages: preliminary understanding, socialization and education, knowledge strengthening, and implementation with post-training assistance. Activities included training on cost accounting concepts, identification of production cost components, application of the full-costing process method, and simple bookkeeping practices. Evaluation results showed a substantial increase in participants’ competencies, with average pre-test and post-test scores improving from 42 to 86. Cost-recording consistency also increased from 20% to 80%, while participants became capable of identifying all cost components involved in COP calculations.The program contributed to improved production management capacity, a transition from trial-and-error costing practices to a systematic full-costing approach, and greater business resilience in responding to market fluctuations. The findings revealed a healthy cost structure, with direct raw materials accounting for 47% and direct labor for 31%. Although challenges remain, particularly weather dependency and high logistics costs, the program successfully transformed informal business practices into a more structured and professional cost management system.